Contrastive rhetoric : reaching to intercultural rhetoric - Connor, Ulla, 1948-; Nagelhout, Ed; Rozycki, William V. (Pragmatics & beyond, 2008)
This volume explores contrastive rhetoric for audiences in both ESL contexts and international EFL contexts, exposing the newest developments in theories of culture and discourse and pushing the boundaries beyond any previously staked ground. The book presents a comprehensive set of empirical investigations involving a number of first languages; 13 of the 17 authors are English-as-a-second-language speakers, many working in non-US contexts. This work develops a coherent agenda for contrastive rhetoric researchers, studying genres such as school writing, grant proposals, business letters, newsp.